Self concept Perempuan Pengemudi Transportasi Ojek Online di Kabupaten Kuningan - Mia Nurislamiah; Budi Rahayu Diningrat (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2020)
The purpose of this research is to describe the reasons for women to be drivers of online motorcycle taxi transportation and to find out the characteristics and self-concept of women driving online motorcycle taxis in Kuningan Regency. This study uses a qualitative method with a phenomenological approach. The data collection techniques used were through observation, in-depth interviews, and documentation study. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the data validity test was checked using the source triangulation technique. The results of this study indicate that female Grab drivers have a positive self-concept. The positive self-concept itself is characterized by several things, such as being able to solve problems, feel equal to others, receiving praise without shame, realizing that everyone has various feelings, and being able to improve themselves. The results of this study also show that the main reason for informants being a Grab driver is not very responsive when people look down on their work.